Structure of pedagogical vocational school teacher technique - Vovkovinsky, Mykola (Professional Pedagogics, 2014)
Pedagogical technique constitutes the basis of all human activities, including pedagogical one. However, technique in educational work as a separate component is not considered but scattered in different technologies and methods leading to good result of training and education in educational institutions. Therefore, the goal of modern researches on pedagogical technique in work of vocational school teachers should gain priority along with theoretical and practical areas as to receiving education at vocational schools. The essence of pedagogical technique consists in the fact that pedagogical skills must be brought to a high degree of perfection, i.e. the degree of pedagogical technique. Only then one can effectively train and educate vocational school students. This paper deals with pedagogical technique as art of training and educating pupils, which represents a high level of realization and perfection of pedagogical skill advanced to the state of the art with the help of a system of verbal-symbolic and context-automatic actions of a teacher (nonverbal and averbal interaction with students); student-targeted and reflective trend which together with special abilities (based on descant receptions) allow to solve educational problems successfully. This allows to adjust work of a teacher in order to maximize the use of his opportunities as regards professional formation of vocational school students. So, pedagogical technique has appropriate internal and external structure, which was foreseen by A.S. Makarenko and confirmed by modern scientists and researchers. Thus, pedagogical technique (technical and situational component) together with tactical training (professional knowledge and providing cognitive activity as a «means of achieving interim results on the way to a strategic goal») should play a major role in the process of training vocational school teachers.